Islamic Education Teachings of K.H. Muhammad Tahir (Imam Lapeo) to the Millennial Generation - Kalam, Abdul; Rahmatullah, Asep (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2025)
The educational teachings of K.H. Muhammad Tahir play a significant role in shaping the character of the millennial generation in the Mandar region. This study aims to analyze the impact of his teachings on the development of character and religious understanding among youth in the modern era. The research employs a library research methodology with a descriptive analysis, involving the collection of data from literature, books, journals, and other written sources. The findings indicate that K.H. Muhammad Tahir’s teachings, through approaches that address spiritual and social aspects, have effectively reduced negative behaviors in the community, such as alcohol consumption, gambling, and cockfighting. Furthermore, the existence of mosques and Islamic boarding schools established as centers for religious education serves effectively in providing access for young people to learn about Islam, particularly through tahfidz classes. The contribution of this research emphasizes the significance of K.H. Muhammad Tahir’s teachings in shaping the character and morals of the millennial generation, highlighting the importance of continuing the legacy of Islamic education amidst the challenges of modernization. This is expected to provide inspiration and deeper understanding of Islamic values for society today.